2015
DOI: 10.4103/1658-354x.146250
|View full text |Cite|
|
Sign up to set email alerts
|

0.5% levobupivacaine versus 0.5% ropivacaine: Are they different in ultrasound-guided sciatic block?

Abstract: Context and Aims:Little is known about onset and duration of sciatic block after 0.5% levobupivacaine (Levo) versus 0.5% ropivacaine (Ropi) for ultrasound-guided technique. We assessed these parameters in the ultrasound-guided block, to know for the practice.Setting and Design:A comparative randomized double-blind study was conducted in the University Hospital.Materials and Methods:Were included 35 adults of ASA I-II, scheduled for foot surgery, presenting clear imaging of their sciatic nerve at mid-thigh. A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Large variations in nerve block duration have been reported previously . The common belief that simply administering more LA will ensure prolonged block duration may not be true, and identifying factors that could decrease this variation is important.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Large variations in nerve block duration have been reported previously . The common belief that simply administering more LA will ensure prolonged block duration may not be true, and identifying factors that could decrease this variation is important.…”
Section: Discussionmentioning
confidence: 93%
“…The minimal relevant effective difference in nerve block duration was considered to be 3 h. Mean (SD) sensory block duration for 5 ml of ropivacaine 0.2% was assumed to be 14 (2.5) h . We estimated the dropout rate to be one subject per trial group.…”
Section: Methodsmentioning
confidence: 99%
“…[ 5 ] Ropivacaine (RB) and levobupivacaine (LB) are enantiomers of bupivacaine that have been compared extensively when administered in neuraxial blocks or other peripheral nerve blocks. [ 6 7 8 ] The present study was undertaken to ascertain the relative analgesic efficacy of these two local anesthetic agents in patients scheduled to undergo PCNL receiving ultrasound-guided PVB.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Studies comparing postoperative analgesia in sciatic nerve block showed that levobupivacaine had a longer duration of postoperative analgesia compared with ropivacaine. [1214] There are four previous studies comparing levobupivacaine and ropivacaine in the same concentrations used for brachial plexus blocks. However, 3 of the studies of brachial plexus block report no difference between these 2 agents.…”
Section: Discussionmentioning
confidence: 99%